Density and Spread Pattern of Carnivore Plant (Nepenthes spp.) In The Area of Sebomban Hill Bonti District, Sanggau - Ternisius Apriyanto; Rafdinal Rafdinal; Sukal Minsas (Jurnal Biologi Tropis, 2021)
Nepenthes spp. is kind of plant that arranged ecosystem in West Kalimantan, especially in the Sebomban hill area, Sanggau Regency. But, its existence is threatened so that several species are included in the endangered category according to the Convention on International Trade in Endangered Species (CITES). The research aims to determine species, community structure, anddistribution patterns of Nepenthes spp. in the area of Sebomban hill, Bonti District, Sanggau Regency. The research method used purposive samplingand systematic sampling with transect. The results showed that there are 3 types of Nepenthes spp. namely N. ampullaria, N. mirabilis and N, gracilis. The density value of Nepenthes spp. ranged from 10 - 45 individual/ ha. The index of importance value of Nepenthes spp. ranged from 42% - 134%, the highest value being Nepenthes ampullaria in location III, while the lowest value was found in location I, namely N. gracilis. All Nepenthes spp. those found at the research location have a pattern of distribution as clustered.